2012
DOI: 10.1155/2012/251865
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach in the Simplification of a Multiple-Beam Forming Network Based on CORPS Using Compressive Arrays

Abstract: This research paper deals with a innovative way to simplify the design of beam-forming networks (BFNs) for multibeam steerable antenna arrays based on coherently radiating periodic structures (CORPS) technology using the noniterative matrix pencil method (MPM). This design approach is based on the application of the MPM to linear arrays fed by CORPS-BFN configurations to further reduce the complexity of the beam-forming network. Two 2-beam design configurations of CORPS-BFN for a steerable linear array are ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The utilisation of the C-BFN to feed a concentric ring and an unequally spaced linear array has been proposed in [10,11], respectively. Also the linear array simplification based on Matrix Pencil method has been proposed in [12] where the radiation pattern has been maintained by using less complex BFN. All of these papers just deal with the array factor and lack the experimental or electromagnetic (EM) full-wave simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The utilisation of the C-BFN to feed a concentric ring and an unequally spaced linear array has been proposed in [10,11], respectively. Also the linear array simplification based on Matrix Pencil method has been proposed in [12] where the radiation pattern has been maintained by using less complex BFN. All of these papers just deal with the array factor and lack the experimental or electromagnetic (EM) full-wave simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The coherent beamforming network delivers a coherent Gaussian-like amplitude tapered excitation law. In addition, this versatile multiple beamforming network have been studied with diverse approaches since its introduction, such as an efficiency analysis of the structure based on the original concept, design and simplification of the coherent network in different antenna array geometries and physical implementations based on enhancements of the feeding network and its basic components [8][9][10]. Although the authors have been addressed the nonuniform linear array fed by a coherent beamforming network in [11], to the best of our knowledge the nonuniform aperture on circular arrays has not been previously analyzed in this feeding network on literature.…”
Section: Introductionmentioning
confidence: 99%
“…This coherent (in-phase) network introduced in [7] is known as coherently radiating periodic structure beamforming network (C-BFN or CORPS-BFN) and generates an in-phase Gaussian-like amplitude distribution. Recent research work based on C-BFN reported approaches for simplifying the network hardware in different antenna geometries, the development of new structures to improve efficiency, and practical implementation of the feeding network [8][9][10][11]. However, the impact of using nonuniformly spaced arrays in C-BFN has not been analyzed previously in the literature.…”
Section: Introductionmentioning
confidence: 99%